Physics qualifying examination :problems and solutions problems and solutions - Farach, Horacio A.; Poole, Charles P.; Safko, John L. (Weinheim : Wiley-VCH, 2010)
This title features a self-study approach to prepare PhD candidates for passing their qualifying examinations. The book presents 120 problems for all relevant physics subjects and is designed to be used in tandem with the 'Handbook of Physics' by C.P. Poole.
Includes bibliographical references and index.
Keywords: Physics -- Examinations -- Study guides; Universities and colleges -- United States -- Entrance examinations -- Study guides; Advanced placement programs (Education) -- Examinations -- Study guides; Theoretische Physik; Aufgabensammlung; Aufgabensammlung